Facing danger: how do people behave in times of need? The case of adult attachment styles - Ein-Dor, Tsachi (Frontiers in Psychology, 2014)
Bowlby’s (1982) attachment theory has generated an enormous body of research and conceptual elaborations. Although attachment theory and research propose that attachment security provides a person with many adaptive advantages, during all phases of the life cycle, numerous studies indicate that almost half of the human species can be classified as insecurely attached or insecure with respect to attachment. It seems odd that evolution left humans in this vulnerable position, unless there are some advantages to individuals or groups, under at least some conditions, of anxious and avoidant attachment styles. I argue that a social group containing members with different attachment patterns may be more conducive to survival than a homogeneous group of securely attached individuals because each attachment disposition has specific adaptive advantages that promote the survival of the individual and people around him or her when facing threats and perils. In making this argument, I extend the scope of attachment theory and research by considering a broader range of adaptive functions of insecure attachment strategies, and present data to support my argument.